A pilot study of online non-invasive measuring technology based on video magnification to determine skin temperature. (15th August 2017) - Cheng, Xiaogang; Yang, Bin; Olofsson, Thomas; Liu, Guoqing; Li, Haibo
Abstract: Much attention was paid on human centered design strategies for environmental control systems of indoor built environments. The goal is to achieve thermally comfortable, healthy and safe working or living environments in energy efficient manners. Normally building Heating, Ventilation and Air Conditioning (HVAC) systems have fixed operating settings, which can't satisfy human thermal comfort requirements under transient and non-uniform indoor thermal environments. Therefore, human thermal physiology signal such as skin temperature, which can reflect human body thermal sensation, has to be measured over time. Several trials have been performed by minimizing measuring sensors such as i-Button and mounting measuring sensors into wearable devices such as glasses. Infrared thermography technology has also been tried to achieve non-invasive measurements. However, it would be much more convenient and feasible if normal computer camera could record images, which could be used to obtain human thermal physiology signals. In this study, skin temperature of hand back, which has a high density of blood vessels and is normally not covered by clothing, was measured by i-button sensors. Images recorded by normal camera were amplified to analyzing skin temperature variation, which are impossible to see with naked eyes. The agreement between i-button sensor measuring results and image magnification results demonstrated the possibility of non-invasive measuring technology by image magnification. Partly personalized saturation-temperature model (T = 96.5 × S + b i ) can be used to predict skin temperatures for young East Asia females. Highlights: Eulerian video magnification technology was used to analyze skin color saturation. Linear relationship between skin color saturation and skin temperature was found. Non-invasive measuring technology was used for measuring human skin temperature. Obtaining control signals of HVAC systems become easy.